Kinetika dan Karakterisasi Amiloglukosidase Isolat Aaspergillus niger Dari Limbah Ampas Sagu - -, Amiruddin (Jurnal Progres Kimia Sains, 2011)
Study of characterization and kinetic amyloglucosidase from Aspergillusniger isolateusing sago pith waste has been done. The aims of this research wereto know the optimumsubstrate concentration, metalions effect, and value of KM and vmaks of amyoglucosidase. Theresult of researches were obtained the optimum activity of amyoglucosidaseat 2% (w/v) ofstarch concentration. The activator of amyoglucosidase were Zn2+, Ba2+, Fe3+, and Co2+,while the inhibitor were Sn2+, Ca2+, Cu2+, Cd2+, Mn2+, Hg2+, and Ni2+. The ions of Hg2+ andNi2+were founded stopped of the enzyme activity. The variables of kinetic of amyloglucosidaewere obtained KM and vmaks value were. 4,40 % , 0,49 mU, respectively.